Leadership-as-practice: Theory and application—An editor's reflection - Joseph A. Raelin (Leadership, 2017)
In this review article, the editor of the new Routledge volume, Leadership-as-Practice: Research and Application, describes the foundation, thematic attributes, and critical uniqueness of leadership-as-practice, comparing it to related collective traditions in leadership and contrasting it to individualistic approaches that emphasize leader psychology. The review highlights the contributions of each chapter writer in weaving a tapestry of an emerging movement seeking to find leadership not in people but within the practices from which it springs.
Keywords: M53; M51; M12; O15; 650; Leadership; Practice; Leadership-as-practice; Leadership development; Process studies